Bio-based and chemical mediated fabrication of silver nanoparticles and evaluation of their potential antimicrobial activity – a comparative view. (1st January 2012) - Prema, P.; Lakshmi Priya, S.; Rameshkumar, G.
Nanotechnology is gaining tremendous impetus in the present century due to its capability of modulating metals into their nanosize. Metallic nanoparticles are traditionally synthesised by wet chemical techniques, where the chemicals used are quite often toxic and flammable. In this work, we describe a cost effective and environment friendly technique for the synthesis of silver nanoparticles from 1 mM AgNO3 solution using microorganism. The bio-based silver nanoparticles in the reaction mixture appeared brown colouration and chemically mediated silver nanoparticles appeared black colouration. The average particle size was 26.25 ± 13.10 nm and 23.75 ± 12.10 nm. The EDS studies of the nanoparticles confirmed the presence of elemental silver signal and no peaks of other impurity. Silver nanoparticles exhibit high antibacterial activity using Staphylococcus aureus as an indicator strain. Bacterial killing kinetics in the presence of fabricated silver nanoparticles exhibit the killing rate of higher activity against Staphylococcus (97.2% and 94.8% respectively). The correlation coefficient between silver nanoparticles and selected bacterial pathogens revealed that there is a strong negative correlation with (r = –0.83 to –0.99).